Impact of physical activity on anxiety among university students: a moderated mediation model - Qin, Tianci; Chen, Ping; Wang, Jiale; Dong, Junwei; Zhang, Kai (Frontiers in Psychology, 2024)
Physical activity among university students significantly influences anxiety, yet the underlying mechanisms require further exploration. This study examines mental toughness as a mediator and social support as a moderator to elucidate these relationships.Methods: Using a cross-sectional design, convenient sampling was employed to select 997 first to fourth-year students from Jishou University for a self-reported survey. Measures included assessments of physical activity, mental toughness, social support, anxiety, and basic demographic variables. Descriptive statistics, correlations, and a moderated mediation model were conducted.Results: Physical activity was significantly negatively correlated with anxiety and positively correlated with mental toughness. Mental toughness was significantly negatively correlated with anxiety, mediating the relationship between physical activity and anxiety to a certain extent. Social support moderated the latter part of the mediated model pathways.Conclusion: Physical activity negatively correlates with anxiety among university students. Mental toughness mediates the relationship between physical activity and anxiety, while social support moderates the latter stages of this mediated model (mental toughness → anxiety).